2012
DOI: 10.1016/j.ijheatmasstransfer.2011.08.047
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of convective heat and mass transfer coefficients for convective drying of a porous flat plate by conjugate modelling

Abstract: Defraeye T., Blocken B., , Analysis of convective heat and mass transfer coefficients for convective drying of a porous flat plate by conjugate modelling, International Journal of Heat and Mass Transfer 55 (1-3), 112-124. http://dx.doi.org/10.1016/j.ijheatmasstransfer.2011. does not require knowledge of convective transfer coefficients (CTCs) but allows determining the CTCs aposteriori, hence identifying their spatial and temporal variability, which is the main focus of this study.Comparison is made with porou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
92
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 30 publications
(46 reference statements)
2
92
0
1
Order By: Relevance
“…The transfer coefficients clearly showed dependency on the surface moisture distribution. Similar results were found by Defraeye et al [14]. To implement these effects of varying transfer coefficients, it is possible to use CFD as a tool to predict the transfer coefficients.…”
Section: Numerical Modelling: Coupling Ham With Cfdsupporting
confidence: 83%
See 1 more Smart Citation
“…The transfer coefficients clearly showed dependency on the surface moisture distribution. Similar results were found by Defraeye et al [14]. To implement these effects of varying transfer coefficients, it is possible to use CFD as a tool to predict the transfer coefficients.…”
Section: Numerical Modelling: Coupling Ham With Cfdsupporting
confidence: 83%
“…With the model, it was possible to predict the microclimate around valuable objects such as paintings. Other attempts of combining CFD and HAM can be found in Mortensen et al [13] and Defraeye et al [14]. Defraeye applied an external coupling procedure and used a separate CFD and HAM model which were then combined by transferring and setting the boundary conditions from one model to the other.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many investigators like Mujumdar, Tsotsas, and Zbicinski have devoted their research to drying mathematical model of conjugated transport of moisture content and heat flux through porous medium [4][5][6][7]. Ranjan et al [8] reported a two-dimensional diffusion model describing the heat and mass, momentum transfer to predict the drying rate of bananas.…”
Section: Introductionmentioning
confidence: 99%
“…Wawrzyniaka et al [11] presented a CFD modeling of heat and mass transfer during spray drying process. Although numerous studies have been published concerning heat and moisture transfer model under different dimensions, mostly in mathematical analysis of the drying rate, the temperature and water content distribution within different materials, cortex effect [12], and the evaporation and diffusion transport properties [13], little literature is available on the effect of thermophysical properties on the convective drying kinetics by taking the conjugated heat and mass transfer effects into account [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Attempts of combining CFD and HAM can be found in Mortensen et al (2007) and Defraeye et al (2012). Defraeye applied an external coupling procedure and used a separate CFD and HAM model which were then combined by transferring and setting the boundary conditions from one model to the other.…”
Section: Introductionmentioning
confidence: 99%